RESEARCH ON STUDENTS' MATHEMATICAL ABILITY IN LEARNING MATHEMATICS IN THE LAST DECADE: A BIBLIOMETRIC REVIEW - Muhammad, Ilham; Angraini, Lilis Marina (JOHME: Journal of Holistic Mathematics Education, 2023)
Mathematical ability is a cognitive ability that needs to be developed in every student because the mathematical ability is closely related to solving problems that involve the relationship of numerical symbols with students' cognitive activities. This study aims to look at the description of previous research related to mathematical abilities in learning mathematics in the last decade using bibliometric analysis methods. The data taken from the Scopus database was refined so that it became 157 publications. The United States of America is the most influential country and has high cooperation with other countries in this field. The focus of this research is: 1) ICT, Augmented reality, Computational thinking, and university; 2) mathematical problems, pre-service teachers, and higher education: 3) mathematics abilities, mathematics literacy, and outcomes; 4) high mathematical ability, technology and critical thinking ability. The results of this study can be used as a reference for future researchers